2016
DOI: 10.1186/s13068-016-0579-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple syntrophic interactions drive biohythane production from waste sludge in microbial electrolysis cells

Abstract: BackgroundBiohythane is a new and high-value transportation fuel present as a mixture of biomethane and biohydrogen. It has been produced from different organic matters using anaerobic digestion. Bioenergy can be recovered from waste activated sludge through methane production during anaerobic digestion, but energy yield is often insufficient to sludge disposal. Microbial electrolysis cell (MEC) is also a promising approach for bioenergy recovery and waste sludge disposal as higher energy efficiency and biogas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(38 citation statements)
references
References 48 publications
2
35
1
Order By: Relevance
“…Because MECs are constantly exposed to wastewater, mixed‐culture biocathode is easier to maintain and economically more viable than pure‐culture biocathode. Mixed‐culture biocathode has been found dominated by Deltaproteobacteria such as Desulfovibrio and Geobacter ,,, in agreement with the previous discussions that these organisms play important roles in HER catalysis. In addition to Proteobacteria, Firmicutes are commonly found in MEC biocathode (Figure ) and are possibly contributing to electron uptake from the electrode and even proton reduction ,.…”
Section: Biocathodesupporting
confidence: 89%
See 2 more Smart Citations
“…Because MECs are constantly exposed to wastewater, mixed‐culture biocathode is easier to maintain and economically more viable than pure‐culture biocathode. Mixed‐culture biocathode has been found dominated by Deltaproteobacteria such as Desulfovibrio and Geobacter ,,, in agreement with the previous discussions that these organisms play important roles in HER catalysis. In addition to Proteobacteria, Firmicutes are commonly found in MEC biocathode (Figure ) and are possibly contributing to electron uptake from the electrode and even proton reduction ,.…”
Section: Biocathodesupporting
confidence: 89%
“…As a consequence of the favorable micro‐environment, CH 4 can account for 86 % of the total biogas . Instead of inhibiting methane production, recent studies used MECs to produce biohythane, an emerging fuel composed of biomethane and 5–10 % biohydrogen . The MEC produced biohythane 80 % faster than an anaerobic digester due to the multiple pathways of biogas production, including fermentative and electrolytic hydrogen production, as well as hydrogenotrophic and electrochemical methanogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentrations of PNP and PAP were determined, as previously reported, and the production was analyzed by a high performance liquid chromatography mass spectrometer (HPLC-MS) ( Wang et al, 2016 ). We used a gas chromatograph (Agilent, 4890D; J&W Scientific, United States) with a flame ionization detector and an appropriate column (19095N-123HP-INNOWAX, 30 m × 0.530 mm × 1.00 μm, J&W Scientific, United States) to analyze the concentrations of volatile fatty acids (VFAs), including acetic acid, propionic acid, isobutyric acid, butyric acid, isovaleric acid, and valeric acid ( Liu et al, 2016 ). The glucose concentration of the cathode effluent was analyzed with a glucose determination kit (RSBIO, Shanghai).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research studies showed that different kinds of substrates including waste biomass could be digested anaerobically in the bioelectrochemical systems (BES) like MFC or MEC [13,20]. However, the complex substrate, such as DS, cannot be directly utilized by exoelectrogens to produce electric current and is usually required participation of different functional groups besides exoelectrogenic bacteria for decomposition [21][22][23]. In fact, the exoelectrogens were able to consume almost all kinds of volatile fatty acids (VFAs) [20,24].…”
Section: Effect Of Short Freezing Timementioning
confidence: 99%